ANALISIS SOFT SKILL, HARD SKILL, DAN SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA MAHASISWA (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2019 UNP Kediri) - Triwahyudi, Ade; Muslih, Basthoumi; Bhirawa, Sigit Wisnu Setya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze soft skills, hard skills, and self-efficacy simultaneously based on student interest. This research uses descriptive research methods, which are methods used to answer questions based on research questions. The results showed that soft skills had no significant effect on student performance, while hard skills and self-efficacy had a significant effect on student performance. The adjusted R² value of 0.625 shows that hard skills and self-efficacy have a significant effect on student entrepreneurship interest. Soft skills also have a positive impact on student entrepreneurship interest. It is important to develop education and training programs that focus on improving soft skills, hard skills, and self-efficacy in the process of increasing students' entrepreneurship interests.